2018
DOI: 10.3390/su10030772
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social-Environmental Performance versus Financial Performance of Banks in Central and Eastern European Countries

Abstract: Abstract:Developed market economies demonstrate a growing interest in issues concerning Corporate Social Responsibility (CSR) and its effects, confirmed by the sizeable theoretical and empirical literature on this issue. A substantial research proves also the positive relation between CSR commitment and financial results of banks in mature markets. However, there is less evidence on CSR existence and its impact in other geographical areas, especially in the research concerning Central and Eastern European Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 68 publications
(90 reference statements)
8
66
0
Order By: Relevance
“…Corporate social responsibility has an impact on project financing. Banks that have better financial efficiency also maintain higher CSR efficiency [39].…”
Section: Corporate Social Responsibility (Csr) and Project Financingmentioning
confidence: 99%
“…Corporate social responsibility has an impact on project financing. Banks that have better financial efficiency also maintain higher CSR efficiency [39].…”
Section: Corporate Social Responsibility (Csr) and Project Financingmentioning
confidence: 99%
“…There are several alternative approaches in devising sustainability report contents (Fijałkowska, Zyznarska‐Dworczak, & Garsztka, ; Schaltegger & Wagner, ; Yongvanich & Guthrie, ) such as the Triple Bottom Line approach, the Intellectual Capital framework or the Balanced Scorecard. Yet the GRI set of guidelines is internationally accepted and constitutes the most widely acknowledged framework for sustainability/nonfinancial reporting.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to the same report, SDGs provide a unique opportunity for companies to create added value through developing, for example, products and services for consumers of low income, improving employees' well-being, as well as that of their contractors along with their suppliers' productivity output (UN Global Compact and KPMG International, 2015). There are several alternative approaches in devising sustainability report contents (Fijałkowska, Zyznarska-Dworczak, & Garsztka, 2018;Schaltegger & Wagner, 2006;Yongvanich & Guthrie, 2006) (Bondy & Starkey, 2012). It should be noted that the external/third-party assurance of sustainability disclosures is of critical importance in the GRI framework as it has a direct effect on the credibility and integrity of the overall nonfinancial accountability process.…”
mentioning
confidence: 99%
“…In addition, it is observed that most of the literature on sustainability in the financial industry, even though it is not related to innovation but to financial performance, is oriented to Western countries, being almost absent in Central and East Europe Countries (CEEC), as compared to developed countries and, therefore, more research in this field is also needed [12]. In fact, sustainability is said to significantly differ between Western and CEE countries (e.g., [13]) and sustainability studies in CEEC are scarce [12]. Countries from CEE are called catching-up or technology followers, using Castellacci's and Archiburgi's [14] term, those with relatively medium-high per capita incomes and relatively well-developed institutions, such as those from CEE countries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our study is contextualized at the intersection of the literature on sustainability-oriented innovation [10,[15][16][17] in the financial industry [10] and in the particular case of catching-up and CEE countries that require further investigation on the topic [12]. This study's goal, therefore, consists of determining whether there is a relationship between innovation and corporate sustainability in the financial industry of catching-up and CEE countries, an exercise not yet accomplished.…”
Section: Introductionmentioning
confidence: 99%